2018
DOI: 10.1186/s41938-018-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of three entomopathogenic fungi, to the aphid species, Metopolophium dirhodum (Walker) (Hemiptera: Aphididae), and their Alkaline protease activities

Abstract: The aim of the present study is to investigate the effect of three entomopathogenic fungi (EPF) (Beauveria bassiana, Cladosporium cladosporioides, and Verticillium alfalfae) on the aphid species, Metopolophium dirhodum (Walker) (Hemiptera: Aphididae). The selected EPF were isolated from the agricultural soil of the National Institute of Plant Protection (INPV) in Constantine, Algeria, and were tested against the aphid insects that were collected from the same area. The aphid species M. dirhodum were exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Efficacy of B. bassiana against M. persicae aphids was evaluated under controlled conditions with the concentration of 1 × 10 7 conidia mL −1 and found that three isolates of B. bassiana (BAU004, BAU018 and BAU019) showed high virulence against test aphids with a mortality of more than 75% [36]. Similarly, the results of our study are in accordance with those found by [29,[37][38][39]. However, the findings of some studies are different from ours.…”
Section: Discussionsupporting
confidence: 90%
“…Efficacy of B. bassiana against M. persicae aphids was evaluated under controlled conditions with the concentration of 1 × 10 7 conidia mL −1 and found that three isolates of B. bassiana (BAU004, BAU018 and BAU019) showed high virulence against test aphids with a mortality of more than 75% [36]. Similarly, the results of our study are in accordance with those found by [29,[37][38][39]. However, the findings of some studies are different from ours.…”
Section: Discussionsupporting
confidence: 90%
“…It was also reported that at concentrations of 10 7 and 10 8 conidia mL −1 of V. lecanii, the maximum mortality rate of M. persicae was recorded as 100% after 12 days of application [40]. Similarly, the effect of B. bassiana on M. persicae was also determined under the controlled condition with the concentration of 1 × 10 7 conidia mL −1 and showed that three strains of B. bassiana (BAU019, BAU004, and BAU018) showed high effect on aphids, with a mortality of over 75% [34,[41][42][43][44]. According to filtrate treatment, our results are similar to results which revealed that degradation of the insect body was observed at higher infiltrate treated aphids, and the reduction of aphid population was higher in higher dose filtrate treatment [27].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of fungi cultures and spore suspensions B. bassiana, V. alfalfae, and T. viride were defined morphologically and isolated from the soil of a wheat field at the National Plant Protection Institute (INPV-National Institute of Plant Protection of Constantine, Constantine, Algeria) following the method of Vinayaga Moorthi et al (2015) and Abdelaziz et al (2018). To isolate the fungi, 1 g of the soil was diluted in 9 ml of sterile distilled water; then, 100 μl from the 10 −3 , 10 −4 , and 10 −5 dilutions of these suspensions was planted on potato dextrose agar (PDA: 200 g potatoes, 20 g glucose, and 20 g agar), supplemented with chloramphenicol (10 mg l −1 ).…”
Section: Production Of Host Plants and Aphidsmentioning
confidence: 99%